Budesonide Multimatrix Is Efficacious for Mesalamine-refractory, Mild to Moderate Ulcerative Colitis: A Randomised, Placebo-controlled Trial - Rubin, David T. (J Crohns Colitis, 2017)
BACKGROUND AND AIMS: Safety and efficacy of budesonide multimatrix, an oral extended-release second-generation corticosteroid designed for targeted delivery throughout the colon, were examined for induction of remission in patients with mild to moderate ulcerative colitis refractory to baseline mesalamine therapy. METHODS: A randomised, double-blind, placebo-controlled, multicentre trial evaluated efficacy and safety of budesonide multimatrix for induction of remission [ulcerative colitis disease activity index score ≥ 4 and ≤ 10] in 510 adults randomised to once-daily oral budesonide multimatrix 9 mg or placebo for 8 weeks. Patients continued baseline treatment with oral mesalamine ≥ 2.4 g/day. RESULTS: Combined clinical and endoscopic remission at Week 8 was achieved by 13.0% and 7.5% of patients receiving budesonide multimatrix [n = 230] or placebo [n = 228], respectively, in the modified intention-to-treat population [p = 0.049]. Clinical remission [ulcerative colitis disease activity index rectal bleeding and stool frequency subscale scores of 0] was similar in both groups [p = 0.70]. More patients receiving budesonide multimatrix vs placebo achieved endoscopic remission [ulcerative colitis disease activity index mucosal appearance subscale score of 0; 20.0% vs 12.3%; p = 0.02] and histological healing [27.0% vs 17.5%; p = 0.02]. Adverse event rates were similar [budesonide multimatrix, 31.8%; placebo, 27.1%]. Mean morning cortisol concentrations decreased at Weeks 2, 4, and 8 with budesonide multimatrix but remained within the normal range. CONCLUSION: Budesonide multimatrix was safe and efficacious for inducing clinical and endoscopic remission for mild to moderate ulcerative colitis refractory to oral mesalamine therapy.